The role of tropical upwelling in explaining discrepancies between recent modeled and observed lower-stratospheric ozone trends - S. M. Davis; N. Davis; R. W. Portmann; E. Ray; E. Ray; K. Rosenlof (Atmospheric Chemistry and Physics, 2023)
Several analyses of satellite-based ozone measurements have reported that lower-stratospheric ozone has declined since the late 1990s. In contrast to this, lower-stratospheric ozone was found to be increasing in specified-dynamics (SD) simulations from the Whole Atmosphere Community Climate Model (WACCM-SD) despite the fact that these simulations are expected to represent the real-world dynamics and chemistry relevant to stratospheric ozone changes. This paper seeks to explain this specific model and observational discrepancy and to more generally examine the relationship between tropical lower-stratospheric upwelling and lower-stratospheric ozone. This work shows that, in general, the standard configuration of WACCM-SD fails to reproduce the tropical upwelling changes present in its input reanalysis fields. Over the period 1998 to 2016, WACCM-SD has a spurious negative upwelling trend that induces a positive near-global lower-stratospheric column ozone trend and that accounts for much of the apparent discrepancy between modeled and observed ozone trends. Using a suite of SD simulations with alternative nudging configurations, it is shown that short-term (∼ 2-decade) lower-stratospheric ozone trends scale linearly with short-term trends in tropical lower-stratospheric upwelling near 85 hPa. However, none of the simulations fully capture the recent ozone decline, and the ozone and upwelling scaling in the WACCM simulations suggests that a large short-term upwelling trend (∼ 6 % decade−1) would be needed to explain the observed satellite trends. The strong relationship between ozone and upwelling, coupled with both the large range of reanalysis upwelling trend estimates and the inability of WACCM-SD simulations to reproduce upwelling from their input reanalyses, severely limits the use of SD simulations for accurately reproducing recent ozone variability. However, a free-running version of WACCM using only surface boundary conditions and a nudged quasi-biennial oscillation produces a positive decadal-scale lower-stratospheric upwelling trend and a negative near-global lower-stratospheric column ozone trend that is in closest agreement with the ozone observations.